Detection of volume loss using the Nexfin device in blood donors. (14th November 2015) - Nicia, S. B.; van Veelen, T. A.; Stens, J.; Koopman, M. M. W.; Boer, C.
Summary: We investigated which haemodynamic parameters derived from Nexfin non‐invasive continuous arterial blood pressure measurements are optimal to detect controlled volume loss in spontaneously breathing subjects. Haemodynamic monitoring was performed in 40 whole‐blood donors. Mean arterial pressure, cardiac index, systemic vascular resistance index and pulse pressure variation were recorded during controlled breathing, and a Valsalva manoeuvre was performed before and after blood donation. Blood donation resulted in a reduction in cardiac index (from 3.96 ± 0.84 l.min −1 .m 2 to 3.30 ± 0.61 l.min −1 .m 2 ; p < 0.001), an increase in systemic vascular resistance (from 1811 ± 450 dyn.s.cm −5 .m 2 to 2137 ± 428 dyn.s.cm −5 .m 2 ; p < 0.001) and an increase in pulse pressure variation (from 13.4 ± 5.1 to 15.3 ± 5.4%; p = 0.02). The area under the receiver operating characteristic curve to detect volume loss was highest for cardiac index (0.94, 95% CI 0.88–0.99) and systemic vascular resistance (0.90, 95% CI 0.82–0.99). Nexfin is a non‐invasive haemodynamic monitor that can feasibly detect volaemic changes in spontaneously breathing subjects.